A review of metrology in lithium-ion electrode coating processes. (1st November 2021) - Reynolds, Carl D.; Slater, Peter R.; Hare, Sam D.; Simmons, Mark J.H.; Kendrick, Emma
Graphical abstract: Highlights: Coating of electrode inks is parameterised and metrology approaches are reviewed. Metrology options are comprehensive, but can be advanced e.g. in-line rheology, particle sizing. Reduced sensor size and cost is required for small scale studies and to develop predictive design. Extensive metrology must be combined to realise the goal of high quality, low-cost production. Abstract: Lithium-ion battery electrode design and manufacture is a multi-faceted process where the link between underlying physical processes and manufacturing outputs is not yet fully understood. This is in part due to the many parameters and variables involved and the lack of complete data sets under different processing conditions. The slurry coating step has significant implications for electrode design and advanced metrology offers opportunities to improve understanding and control at this stage. Here, metrology options for slurry coating are reviewed as well as opportunities for in-line integration, discussing the benefits of combining advanced metrology to provide comprehensive characterisation, improve understanding and feed into predictive design models. There is a comprehensive range of metrology which needs little improvement to provide the relevant quantifiable measures during coating, with one exception of particle sizing, where more precise, in-line measurement would be beneficial. However, there is a lack of studies that bring together the latest advancements in electrode coating metrology which is crucial to understanding the interdependency of myriad processing and product parameters. This review highlights the need for a comprehensive metrological picture whose value would be much greater than the sum of its parts for the next generation of multiphysics and data-driven models.